Manajemen Reputasi Trustco Persada terhadap Konsumen - Thoifur Humam Hanif; Muhammad Ghani Hadiatul Haq; Muhammad Hussain Ramadhan; Kholifatul Fauziah (Yayasan Literasi Sains Indonesia, 2023)
The company's reputation is important to each company because it is the sum total of what people think about the company. For a company, managing and maintaining a reputation is more complex than just selling products or services to consumers. It takes time for a company to establish a reputation and when it is established, and it can be difficult to maintain it, since there must be many competing interests in the same field. Researchers are interested in researching how reputationco persada management. The nature of the research used is qualitative descriptive using qualitative research methods. Data obtained through in-depth interviews and documentaries. Research shows that it has continued to suppress and improve the quality of service and products, as well as to add new collaborative networks and also never to reject orders at a fraction of the cost. This made it possible for persco persada to maintain its reputation, one of which was the costly ordering from the vanity